Flexible riser replacement operation based on advanced virtual prototyping. (15th August 2020) - Yuan, Shuai; Major, Pierre; Zhang, Houxiang
Abstract: As a critical campaign in the offshore oil and gas engineering, flexible riser replacements involve complex operations that need to be optimized and detailed to factor in trends in the industry. Since it allows engineers to interact with simulation tools in real time during the operation design phase, virtual prototyping (VP) is an efficient method to obtain an optimal solution and improve operational procedures in terms of safety and effectiveness for risk-based integrity management of flexible risers. In this study, a real-time VP model is adopted to simulate the process of a water injection flexible riser pulled in from an installation vessel to a jacket platform, which is one of the riser replacements tasks. The results are validated against results based on a finite element analysis. Attention is paid to the configuration, tension, and maximum bending curvature along the flexible riser during the operation. The innovative approach presented in this paper can provide guidance with respect to the operation limitations of a flexible pipe in practical engineering. Graphical abstract: Image 1 Highlights: A virtual prototyping (VP) framework for the riser replacement operation is applied. This framework integrates virtual reality, real-time and humans in the loop. A finite element model is provided for the consistent procedures of riser pull in. The mechanical responses of riser are well predicted based on both VP and FEA models.